A Comparative Study on Physical Growth and Nutritional Status between Chakma and Riang Adolescent Boys of Tripura, Northeast India: A Study on Physical Growth and Nutritional Status of Chakma and Riang Adolescent Boys in Tripura, India (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Background Growth and nutritional status is a major public health concern for children and adolescents of developing countries such as India and causes high mortality and morbidity.Objective To assess the prevalence of malnutrition among Chakma and Riang adolescent boys of North and Dhalai district of Tripura, a Northeastern state of India.Method A cross-sectional study was carried out among 778 (Chakma 391 nos. and Riang 387 nos.) ethnic adolescent boys aged 8-14 years of North and Dhalai district of Tripura, Northeast India. Height and weight were recorded and the body mass index was calculated. WHO recommended indices of stunting (height-for-age, ˂-1 and ˂-2 Z score level), thinness (BMI-forage,